2019
DOI: 10.3389/fnagi.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

Activated Microglia in Cortical White Matter Across Cognitive Aging Trajectories

Abstract: Activation of microglia, the primary mediators of inflammation in the brain, is a major component of gliosis and neuronal loss in a number of age-related neurodegenerative disorders, such as Alzheimer’s disease (AD). The role of activated microglia in white matter, and its relationship with cognitive decline during aging are unknown. The current study evaluated microglia densities in the white matter of postmortem specimens from cognitively normal young adults, cognitively normal older adults, and cognitive “S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…This early inflammation was also supported by PET-imaging of microglial activation in white matter (60). In a quantitative approach one group investigated microglial density in white matter of cognitively normal young and old individuals (40-100 year of age) showing higher levels of microglial activation in old cases compared to young and the very old (25). In our cohort, we had two white matter regions, BA46 and CG, which showed increased HLA-DR-positive microglia in AD compared to control.…”
Section: Discussionmentioning
confidence: 87%
“…This early inflammation was also supported by PET-imaging of microglial activation in white matter (60). In a quantitative approach one group investigated microglial density in white matter of cognitively normal young and old individuals (40-100 year of age) showing higher levels of microglial activation in old cases compared to young and the very old (25). In our cohort, we had two white matter regions, BA46 and CG, which showed increased HLA-DR-positive microglia in AD compared to control.…”
Section: Discussionmentioning
confidence: 87%
“…These data indicate a robust neuroinflammatory response to DAI in the DG, where the response in males was larger than females, similar to that previously reported after a focal injury (controlled cortical impact) in mice ( 113 ), but not after mFPI in mice ( 114 ). In our study, we did not follow-up with any behavioral tests to confirm cognitive deficits, but other studies showed that midline FPI-induced age-related microglial activation in the hippocampus was directly related to cognitive decline ( 115 117 ).…”
Section: Discussionmentioning
confidence: 88%
“…Evidence indicates that aged brains undergo several pathological changes: higher metabolic stress, reduced neurogenesis, increased synaptic aberrations, immune dysregulation (high expression of inflammatory markers), and low expression of neuroprotective factors. Altered brain physiology, along with disturbances in the function and synchronization of the circadian system, significantly increase the prevalence of neurodegeneration, neurobehavioral deficits, and cognitive aging [ 7 , 8 ]. Research documents that normal cognitive aging involves synaptic changes and decreased neuronal plasticity of the cortex and hippocampus, which directly accelerate declines in memory, reasoning, and speed; these alterations may start from early adulthood [ 9 , 10 ].…”
Section: An Overview Of Cognitive Agingmentioning
confidence: 99%
“…A sensitized phenotype of the aged brain is highly vulnerable to secondary insults such as infections and psychological stress. Inflammatory cytokines foster the transcriptional upregulation of β-secretase and APP and increase Aβ aggregation, which contribute to the characteristic neuropathologic substrate of AD—Aβ plaques [ 7 , 11 , 33 ].…”
Section: The Mechanism Underlying Ad Developmentmentioning
confidence: 99%
See 1 more Smart Citation